Victorian culture and classical antiquity art, opera, fiction, and the proclamation of modernity - Goldhill, Simon (Martin classical lectures, 2011)
How did the Victorians engage with the ancient world? Victorian Culture and Classical Antiquity is a brilliant exploration of how the ancient worlds of Greece and Rome influenced Victorian culture. Through Victorian art, opera, and novels, Simon Goldhill examines how sexuality and desire, the politics of culture, and the role of religion in society were considered and debated through the Victorian obsession with antiquity.